The influence of individualizing physical loads on speed, creatin kinase activity and lactate dehydrogenase in football players - Andrzejewski, M.; Chmura, J. (Biology of Sport, 2008)
One of the most important training problems in: contemporary football is speed preparation of a player for the season and the ability of keeping it on the same, relatively high level throughout the starting period [1]. The main process used for re-synthesis ATP during single, short-lasting efforts of maximal intensity, is decomposition of phospho-creatine under the influence of creatine kinase enzyme. Physical loads imposed during speed trainings often exceed the possibility of producing energy frorn phosphogenic reserve through oxygen - lactate free processes, because the supply of phospho-creatine is used very quickly. In such circumstances the lacking energy is refilled through processes called oxygen free glicolise with the help of lactate dehydrogenase enzyme. The aim of the work was to answer the question: "Does the individualization of physical loads influence the change of speed, creatine kinase activity and lactate dehydrogenase in young football players in six-month makrocycle?". Materials and Methods: The research was done on the group of 19 13-year-olds team players of WKP "Lech" Poznan. The stages of the research were conducted in six-month macrocycle. The average height of the players was 159,69+8,5 cm, and weight 48,06 +8,02 kg. The players had practiced football for four years. To complete the research the following methods were used: 1) players were divided into two motor types: speed and endurance. This was done on the basis of the speed results frorn three distances 20, 30, and 40 m.; 2) physical toads individualization was introduced. In each microcycle three series of six repetitions of speed exercises connected with coordination elements were used. For each motor type of players researchers used individual physical load program concerning the length of race and breaks of active rest; 3) At the beginning of the preparation period and before and after starting period the time of 30 m. distance was measured; 4) While resting and on a third minute after completing the endurance test the researchers took 5 ml of blood. In Order to mark creatine kinase activity and lactate dehydrogenase the authors used diagnostic test Cormay and Spektrofotometr SEMCO S91E. Results: Individualization of physical loads during speed training for both types of players causes the change of creatine kinase activity and lactate dehydrogenase as well as influences the development of speed abilities of young footballers in six-month makrocycle. The conducted research of locomotive speed on 30 m. distance proved that for both types of players the ability rises.